Measuring consumer preference for models of diabetes care delivered by pharmacists - Chou A; Hsu TH; Lee CC; Kuei-Lien Su C; Wang Y; Norris P; Chong CE (Centro de Investigaciones y Publicaciones Farmaceuticas, 2009)
Gaps in public knowledge about antibiotics have led to calls for public education campaigns about antibiotics, including education of school children.Objective: This study investigates New Zealand primary school teachers' current level of knowledge about antibiotics, to assess whether this is adequate for providing accurate education for children. Methods: Two hundred and sixty-six primary school teachers from 39 schools in four cities were interviewed about their knowledge and understandings of antibiotics, using a questionnaire. Results: Teachers reported having little current involvement with antibiotics. There were gaps in the understanding of antibiotics amongst many of the teachers. Only about 60% knew that antibiotics were useful only in bacterial infections, many believed antibiotics were useful for colds and flu, and many did not know about antibiotic resistance. On the other hand, teachers largely reported appropriate patterns of antibiotic use. Conclusion: If teachers are to educate children about antibiotics, basic education about antibiotics and resistance will be required for school teachers.